Está en la página 1de 3

4

Module 1. Matrices

Exercise 1.1.1.
Evaluate the following determinants:

1.

5.

9.



3 1


2 4



 1
5 

2. 
6 11 



5 0 1 


 2 1 1 


3 2 0 



 1
3 5 

0 9 
6.  0
 2 3 1 



5 2
0 

 0 6 1 


1 1
3 

3.

7.



x 2 


 y 3 

4.



i j k


 1 1 2 


3 2 1

8.



2 0


5 7


 1 1 1 


 3 5 3 


4 7 4



 2 1
3 

4
0 
10.  0
 4 2 6 

11. An element of a lamina is subjected to normal


 12 and
 tangential stresses on each of its
8
four sides. The associated stress matrix is A = 8
15 . Calculate the principal stresses,
given that each principal stress, , satises det(A I) = 0

15
8
8

12

12

8
8
15

Answers to Exercise 1.1.1.


1.
5.
9.

10
11
87

1.2
1.2.1

2. 41
6. 27
10. 0

3. 3x 2y
7. 5i + 5j + 5k
11. 21.64; 5.36

4.
8.

14
0

Cramers rule
Cramers rule for two unknowns

To solve
ax + by = e

(1.2.1)

cx + dy = f

(1.2.2)

adx + bdy = de

(1.2.3)

bcx + bdy = bf.

(1.2.4)

multiply (1.2.1) by d and (1.2.2) by b

1.2. Cramers rule

Equation (1.2.3) equation (1.2.4) adx bcx = de bf


x(ad bc) = de bf
de bf
x=
ad bc
In determinant form, (1.2.5) can be written as
eb

f d
x =  a b
c d

or
x=

(1.2.6)

1
,

(1.2.7)



a b
.

and = 
c d



e b


1 = 
f d

where






(1.2.5)

The determinant contains the coecients of x and y, while 1 is obtained from by


replacing its rst column with the constants on the right-hand sides of (1.2.1) and (1.2.2).
Similarly, it can be shown that
y=

2
,

(1.2.8)



a e 
.

2 = 
c f

where

The determinant 2 is obtained from by replacing its second column with the constants
on the right-hand sides of (1.2.1) and (1.2.2).
Equations (1.2.7) and (1.2.8) taken together are known as Cramers rule for two unknowns.
Example 1.2.1. For the electric circuit shown, the equations for the electric currents (i1
and i2 in amperes) are given:
8i1 3i2 = 2

3i1 + 10i2 = 6.

Solve the equations using Cramers rule for two unknowns.

2V

i1

i2

6V
5

Module 1. Matrices

Solution



1
=
i1 =


=
=
=

i2 =

1.2.2

2
6
8
3

3
10
3
10






(2)(10) (3)(6)
(8)(10) (3)(3)
20 + 18
80 9
2
amps.
71
 8 2 


42
6
=
=  3
amps
8
3


71
3 10

Cramers rule for three unknowns

To solve
a1 x + b1 y + c1 z = k1 ,

(1.2.9)

a2 x + b2 y + c2 z = k2 ,

(1.2.10)

a3 x + b3 y + c3 z = k3 ,

(1.2.11)

we can rst eliminate z from the rst two equations by multiplying the rst by c2 and the
second by c1 and then subtracting. We then obtain the equation
(a1 c2 a2 c1 )x + (b1 c2 b2 c1 )y = k1 c2 k2 c1 .

(1.2.12)

Then we can eliminate z from equations (1.2.10) and (1.2.11) by multiplying (1.2.10) by c3
and (1.2.11) by c2 and then subtracting. We then obtain the equation
(a2 c3 a3 c2 )x + (b2 c3 b3 c2 )y = k2 c3 k3 c2

(1.2.13)

Equations (1.2.12) and (1.2.13) can be solved for x and y using Cramers rule for two
unknowns, giving
(k1 c2 k2 c1 )(b2 c3 b3 c2 ) (k2 c3 k3 c2 )(b1 c2 b2 c1 )
(a1 c2 a2 c1 )(b2 c3 b3 c2 ) (a2 c3 a3 c2 )(b1 c2 b2 c1 )
(a1 c2 a2 c1 )(k2 c3 k3 c2 ) (k1 c2 k2 c1 )(a2 c3 a3 c2 )
.
y=
(a1 c2 a2 c1 )(b2 c3 b3 c2 ) (a2 c3 a3 c2 )(b1 c2 b2 c1 )

x=

(1.2.14)
(1.2.15)

If we expand the terms in the numerator (top line) and denominator (bottom line) of
(1.2.14), we obtain
x=

c2 (k1 b2 c3 k1 b3 c2 k2 b1 c3 + k2 b3 c1 + k3 b1 c2 k3 b2 c1 )
c2 (a1 b2 c3 a1 b3 c2 a2 b1 c3 + a2 b3 c1 + a3 b1 c2 a3 b2 c1 )

which simplies to
x=

k1 b2 c3 k1 b3 c2 k2 b1 c3 + k2 b3 c1 + k3 b1 c2 k3 b2 c1
.
a1 b2 c3 a1 b3 c2 a2 b1 c3 + a2 b3 c1 + a3 b1 c2 a3 b2 c1